A reforma da educação profissional de nível médio no Brasil: um debate sobre a pedagogia das competências e o trabalho como princípio educativo - Silva, Camila Aparecida da (2020)
This research aims to study the curriculum conceptions that guided the reforms of contemporary technical professional education, specifically the aspects that defined these reforms: the concepts of competence and work as an educational principle. The main question that guided this work was – How do official documents for high school vocational education incorporate the debate on skill pedagogy ad work as in educacional principle? Thereby, the general objective of this research is to find out how the professors of the IFSP mechanics course understand the reforms, its different conceptions, and foundations expressed in the different decrees and curricular guidance documents. In order to achieve this objective, we analyze documents about some reforms of technical and vocational secondary education proposed by the Ministry of Education (MEC) that discuss the curriculum (Decrees 2208/97 and 5154/04), specifically the concepts that underlie them, and the way of these concepts can be incorporated into curriculum reference documents produced within the scope of the IFSP. Beyond the analyzes of documents set described, the legislation of technical professional education of secondary level in Brazil, mainly the Decrees, the National Curricular Guidelines, and the curricular documents produced by the IFSP, the present research are constituted by a set of semi-structured interviews with professors from the São Paulo campus, of the Technical Course in Mechanics Integrated to High School. The results showed that the teachers interviewed have a preference and a closer relationship with the Pedagogy of Competences, a fact that can be explained by the nature of the course, in which a naturalized logic in the industry predominates, expressed by them in the school institution. We could also observe how the teachers react to those policies in different ways. In summary, if the reforms propose changes that reaffirm their convictions, as was the case with the reform via Decree 2.208, they react in order to validate the reform. If the reform proposes changes in their practice and a different perspective, as occurred in the context of Decree 5.154 / 2004, they present a greater resistance.